I Know it, so I do not Need to Touch it: Role of Brand Familiarity in Tactile Product Evaluation - Jha, Subhash; Balaji, M. S. (Indian Journal of Marketing, 2015)
The purpose of this study was to examine the role of brand familiarity in tactile product evaluation. The results of the two experimental studies showed that individual differences in need for tactile input affect purchase intentions depending upon the structure of the choice environment and familiarity levels of a brand. The well-developed knowledge structures for familiar brands allow consumers to access the diagnostic tactile cues from their memory in product assessment in an online environment. Conversely, for less familiar brands, the inaccessibility of predictive tactile cues in an online shopping environment reduces the purchase intentions. This study makes three important contributions. First, it showed that tactile inputs have a positive effect on purchase intentions in the touch environment, particularly for individuals with high levels of need for tactile input. Second, it posited that the lack of tactility can be overcome by offering familiar brands in the no-touch environment. Finally, it showed that for low need tactile input individuals, lack of tactility does not impede them from making online purchases. The paper discussed the implications of research findings and offered future research avenues along with limitations.